Digital Game-based Learning for Early Childhood - PEIRCE, NEIL (Learnovate Centre, 2013)
This report presents a comprehensive review of the research evidence for the effectiveness of digital game-based learning for early childhood learning. The report also identifies the types of learning content suited to a digital games-based learning approach and outlines key considerations when designing games for early childhood.
PUBLISHED
Keywords: learning; games; early childhood; education; Intelligent Content & Communications